The Application of the Foral Successory Law to Foreigners: Back with the Civil Neighborhood - Castellanos Ruiz, Esperanza (CUADERNOS DE DERECHO TRANSNACIONAL, 2022)
This commentary deals with the problem, doctrinally not at all peaceful, on the application of Foral Inheritance Law to foreigners residing in Spain, as a consequence of the designation of the Spanish law, through the norms contained in the European Regulation 650/2012. Bearing in mind that the Spanish legal system is multi-legislative with a territorial basis, the application of regional law to foreigners is proposed through the solution contemplated in art. 36 of the Inheritance Regulation. For this, the RDGSJFP of January 20, 2022 will be studied, where the application of the Galician Inheritance Law to a French national residing in Galicia is proposed.